PENGARUH IMPLEMENTASI PEMBELAJARAN PENDIDIKAN PANCASILA BERBASIS KURIKULUM MERDEKA DALAM MEMBENTUK GOOD CITIZEN DI KELAS VIII SMP NEGERI 24 MEDAN - MANURUNG, ANNA MAUDINA; YUNITA , SRI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to determine the influence of the implementation of Pancasila Education learning based on the Merdeka Curriculum implemented by teachers in forming good citizens in class VIII students at SMP Negeri 24 Medan. The research method used in this research is mix methods, a descriptive correlation type of research, with data collection techniques through observation, interviews, and questionnaires. In this study, the population was used, namely all class VIII students, totaling 350 students, and the sample in this study was 15% of the total number of class VIII students, namely 53 students, using the proportionate stratified random sampling technique. Then data analysis is carried out based on data on variables x and y with the hypothesis that if tcount is greater than ttable then the working hypothesis (Ha) is accepted and (Ho) is rejected, conversely if tcount is smaller than ttable then the working hypothesis (Ha) is rejected and (Ho) is accepted . Based on the research results which have been analyzed using the product moment correlation formula, the rcount value is 0.557 which is greater than the rtable value of 0.270 at a significance level of 5% with degrees of freedom (dk) = n-2 (53-2 = 51) so we get ttable = 0.270 , and the results of the